Super-Enhancer Induced IL-20RA Promotes Proliferation/Metastasis and Immune Evasion in Colorectal Cancer - Yu, Dingye; Yang, Xiao; Lin, Jianwei; Cao, Zichao; Lu, Chenghao; Yang, Zheyu; Zheng, Minhua; Pan, Ruijun; Cai, Wei (Frontiers in Oncology, 2021)
Unveiling key oncogenic events in malignancies is the key to improving the prognosis and therapeutic outcome of malignancies. Lines of evidence have shown that super-enhancers control the expression of genes that determine the cell fate, but the oncogenic super-enhancers in colorectal cancer (CRC) and their impact on carcinogens remain largely unexplored. Here, we identified a new oncogenic super-enhancer-regulated gene, IL-20RA, in CRC. Using the integrative analysis of H3K27ac ChIP-seq and RNA-seq in CRC tumors and normal colon tissues, we obtained a series of oncogenic super-enhancers in CRC. We found that super-enhancer inhibition by JQ-1 or iBET-151 suppressed the growth of tumor cells and inhibited the expression of IL-20RA. We found that IL-20RA was highly expressed in the tumor tissue of CRC and related to the advanced stage. Further functional studies showed that knockdown of IL-20RA inhibited the growth and metastasis of CRC. In addition, we found that IL-20RA was involved in regulating oncogenic and immune pathways and affecting the expression of genes related to cell proliferation and immune evasion in CRC. Together, our study demonstrated a novel oncogene in CRC and shed new light on oncogenic super-enhancer contributions to cell proliferation and immune escape.